2019
DOI: 10.1111/jpm.12566
|View full text |Cite
|
Sign up to set email alerts
|

The use of positive behaviour support plans in mental health inpatient care: A mixed methods study

Abstract: Accessible summary What is known on the subject? There is a drive to use positive and proactive approaches to mental health care to reduce the use of restrictive practices such as seclusion and restraint. Positive behaviour support plans have been used successfully to do this in learning disability services, and in England, it is now a regulatory requirement that anyone with challenging behaviour should have an individualized behaviour support plan. However, positive behaviour support plans specifically have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…We have contributed a preliminary conceptual framework to comprehensively describe the competences healthcare professionals need to successfully manage challenging behaviours. Conceptual clarity is needed, as inadequate conceptual understanding of the competences required for behaviour management may lead to ineffective implementation on interventions (Clark et al., 2020; Price et al., 2016; Tölli et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have contributed a preliminary conceptual framework to comprehensively describe the competences healthcare professionals need to successfully manage challenging behaviours. Conceptual clarity is needed, as inadequate conceptual understanding of the competences required for behaviour management may lead to ineffective implementation on interventions (Clark et al., 2020; Price et al., 2016; Tölli et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…BPS has increased staff confidence in a forensic medium secure unit (Davies et al., 2015). Although Clark et al (2020) recognized the potential of PBS to improve psychiatric care, they found that staff were still not always competent at identifying behaviours of distressed people. The successful implementation of Safewards, PBS and other training interventions is connected to staff competence, and comprehensive understanding of staff competence in behaviour management is needed to ensure that these interventions are as effective as possible.…”
Section: Discussionmentioning
confidence: 99%
“…47 Clinicians not following or engaging in the intervention protocol was similarly reported in other studies. 29,33,37,46,51,52,59,74,99,100 More experienced clinicians were found to be associated with lower completion rates of crisis plans with service users. 81 In addition, several studies reported that substantial effort or support was required for clinicians to change their approaches and routine practices.…”
Section: Ii) Mental Health Professionalsmentioning
confidence: 95%
“…For example, clinicians were reported as being disrespectful of service users by being inconsistent (saying or promising one thing and doing something else), condescending, patronising and judgemental, by not listening, not taking the time to explain matters and not respecting service users' wishes. 29,42,47,50,51,64,71,84,86,96,97 Furthermore, many clinicians were resistant to changing their practices to accommodate shared or supported decision-making in treatment planning. For example, in one study, no psychiatrists went to service-wide training attended by 350 other health professionals.…”
Section: Ii) Mental Health Professionalsmentioning
confidence: 99%
“…4 Disruptive patient behavior occurs in inpatient psychiatric settings with a lax ward structure, unclear and inconsistent implementation of hospital rules, and poorly defined staff roles. 1,[5][6][7] However, the impact of disruptive or unsafe behaviors on patient care in EDs and nonpsychiatric medical inpatient units is not well reported. This article explores the use of a behavior support plan (BSP) to address disruptive patient behaviors and ensure the safe delivery of patient care.…”
mentioning
confidence: 99%